Age at pubarche and the risk of developing cardiometabolic complications among 50–52-year-old men from Krakow Longitudinal Study (Poland) - Spring, Barbara Anna; Woronkowicz, Agnieszka; Żarów, Ryszard; Kowal, Małgorzata (Anthropological Review, 2024)
Despite contradictory observations, it has been postulated that early age of adrenarche predisposes to an increased risk of cardiometabolic complications in further ontogeny due to greater body fatness. The aim of this study was to test the above postulates. We present the results of research on 67 men aged 50–52 – participants of the Krakow Longitudinal Study conducted in the years 1976–2022 – from two birth cohorts 1970 and 1972. Boys were examined annually, aged 6–18, initially 940 people, at the age of eighteen – 358. They were examined again as adult men in 2004 (age 32–34) – 122 people and again in 2022 (age 50–52 years) 67 men. Based on the pubarcheal age, 50-year-olds were divided into 3 groups: early (11 people), average maturing (44 people) and (12 people), where the following were compared: resting systolic and diastolic blood pressure, basic parameters lipid profile – total cholesterol and its fractions, triglycerides, fasting glucose, body height and weight, waist and hip circumferences, indicators – Body Mass Index (BMI), Waist–hip Ratio (WHR), the thickness of 6 skinfolds and the prevalence of metabolic syndrome. The results of the analyses showed that: (1) there is a clear gradation, i.e., the earlier the age of pubarche, the worse the metabolic health of men; (2) compared to the other groups, the total adiposity in men with early pubarche is slightly higher, with clearly marked abdominal obesity; BMI and WHR showed a contrasting picture. At this stage of the analyses, it is difficult to clearly judge whether the cause of the increased cardiometabolic risk in the studied men with early pubarche is related to earlier age of adrenarche and the mechanisms and stimuli causing it, or to greater adiposity.